Does Participative Leadership Matters in Employees’ Outcomes During COVID-19? Role of Leader Behavioral Integrity - Usman, Muhammad; Ghani, Usman; Cheng, Jin; Farid, Tahir; Iqbal, Sadaf (Frontiers in Psychology, 2021)
The coronavirus pandemic (COVID-19) has badly affected the social, physical, and emotional health of workers, especially those working in the healthcare sectors. Drawing on social exchange theory, we investigated the effects of participative leadership on employees’ workplace thriving and helping behaviors among frontline workers during the COVID-19 pandemic. In addition, we examined the moderating role of a leader’s behavioral integrity in strengthening the relationship between participative leadership, and employees’ workplace thriving and helping behaviors. By using a two-wave time-lagged design and data collected from 244 healthcare workers, a moderated hierarchal regression was implemented to test the proposed hypotheses. As hypothesized, participative leadership predicted employees’ workplace thriving and helping behaviors. The leader’s behavioral integrity strengthened the relationship between participative leadership and employees’ thriving and moderated the relationship between participative leadership helping behaviors. Implications for research, theory, and practice are discussed.